1972
DOI: 10.1126/science.176.4030.78
|View full text |Cite
|
Sign up to set email alerts
|

Motion Perception: A Color-Contingent Aftereffect

Abstract: When observers who watched repeated alternations of a red contracting spiral and green expanding spiral were later shown stationary spirals, red and a green the red stationary spiral appeared to be expanding and the green stationary spiral appeared to be contracting. These color-contingent motion after effects complement reports of motion-contingent color aftereffects and suggest that both may reflect adaptation of detectors specific to color and motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
50
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 7 publications
4
50
0
Order By: Relevance
“…He had 121 naive observers inspect a spiral display for 15 minutes and found that he could measure MAEs from 20 to 26 hours later. These results have been replicated by Kaflin and Locke (1972), and Favreau, Emerson, and Corballis (1972). ihe latter report that after 24 hours the effect is weak and fades in 5 sec.…”
supporting
confidence: 78%
“…He had 121 naive observers inspect a spiral display for 15 minutes and found that he could measure MAEs from 20 to 26 hours later. These results have been replicated by Kaflin and Locke (1972), and Favreau, Emerson, and Corballis (1972). ihe latter report that after 24 hours the effect is weak and fades in 5 sec.…”
supporting
confidence: 78%
“…Hepler (1968) reported that motion-contingent color aftereffects are still seen about 24 h after adaptation. Favreau et al (1972) found that color-contingent motion after-effects, too, can persist for at least 24 h. Stromeyer and Mansfield (1970) reported a few instances in which motion-contingent color aftereffects were still present 5 to 6 weeks after the initial adaptation period. A number of authors have reported that the McCoIlough effect can persist for fairly long periods of time (e.g., Mackay & Mackay, 1975;Riggs, White, & Eimas, 1974;Shute, 1977), but by far the longest persistence periodhas been reported by Jones and Holding (1975).…”
mentioning
confidence: 99%
“…For example, by using appropriate adapting conditions, a color aftereffect can be made contingent on the direction of motion of a grating (Hepler, 1968;Stromeyer & Mansfield, 1970) or on its spatial frequency (Lovegrove & Over, 1972). Conversely, apparent orientation (Held & Shattuck, 1971) or direction of motion can be made contingent on color (Favreau, Emerson & Corballis, 1972;Mayhew & Anstis, 1972).…”
mentioning
confidence: 99%
“…the McCollough effect, an orientation-contingent color aftereffect (McCollough, 1965); a colorcontingent orientation aftereffect (Held & Shattuck, 1971); motion-contingent color" aftereffects (Hepler, 1968;Stromeyer & Mansfield, 1970); color-contingent motion aftereffects (Favreau, Emerson, & Corballis, 1972); and texture-contingent visual motion aftereffects (Mayhew & Anstis, 1972;Walker, 1972). In each case, during an inspection period, there is a pairing of two sensory dimensions-such as color and orientation or size and position.…”
mentioning
confidence: 99%